A proposed FPGA Architecture Design - Mulualem, Yelkal; Sirajudeen, M.Mohamed (IJRDO-Journal of Applied Science, 2015)
This research paper discuss with a general over view of FPGAs particularly, Architectural Descriptionof Virtex-4 FPGA and Verilog Hardware Description Language of the proposed work. It has also depthdescription of design of the new developed FPGA Architectural. FPGA architecture design anddevelopment approach used in this paper is followed top-down approach. Later the design andimplementation of the four modules, namely, Top-Module, Read-Code Word Module, ReadAveragedSample Module and Decoder-Module will be discussed with the necessary information’s.